Etude de quelques caractères probiotiques de ferments lactiques - MOSTEFAOUI, ZOULIKHA; BRAHIMI, LYDIA (My University, 2023)
Lactic ferments, also known as lactic bacteria, are beneficial microorganisms present in many fermented foods like traditional dairy products such as Zebda, Lben and fresh cheese. Some strains of lactic bacteria beneficial to health are called probiotics. Probiotics confer health benefits when consumed in adequate amounts. Research has shown that probiotics can have a variety of beneficial effects, including regulating the balance of gut flora and boosting the immune system. The objective of our work was the isolation and identification of lactic strains from traditional dairy products. After their isolation, phenotypic characterization tests were carried out for purification. Then, the different biochemical and physiological tests that should be performed for the identification of isolates. In the end, tests were established to study some probiotic effects. A total of 5 strains of lactic bacteria were isolated and identified. The results show the presence of different genera: Leuconostoc, Lactococcus, Lactobacillus and Bifidobacterium. The 5 isolates resisted the conditions of the intestinal flora and have a good inhibitory power against some species of pathogenic bacteria responsible for various diseases in humans. Keywords:
Keywords: traditional dairy products; lactic acid bacteria; probiotics